LEIOMYOSARCOMA OF THE INFERIOR VENA CAVA MASQUERADING AS A DUODENAL STROMAL TUMOUR - Faisal Ali; Asfand Bangash; Butt, Muhammad Abdurrahman; Sibgha Aimon; Rabia Saleem; Muslim Atiq; Khan, Hadi Mohammad (Journal of Ayub Medical College Abbottabad, 2024)
Leiomyosarcomas originating in the inferior vena cava (IVC) are rare vascular tumors characterized by gradual growth and subtle onset. The challenges associated with these tumors stem from their unfavorable prognosis and the absence of established treatment protocols. We present a case of a 52-year old woman who presented with abdominal pain and was subsequently diagnosed with leiomyosarcoma in the second segment of the IVC. This case highlights the significance of adopting a multidisciplinary approach and emphasizes the necessity for timely identification and intervention in IVC leiomyosarcomas to improve patient outcomes. To our knowledge, this is the first reported case of leiomyosarcoma in the IVC from Pakistan. We believe this case will contribute valuable insights to the existing knowledge on the subject.